Concurrent Stroke and Myocardial Infarction After Mild COVID-19 Infection - Ruiz-Ares, Gerardo (Neurologist, 2021)
The concurrency of both, acute stroke and acute myocardial infarction in normal conditions, outside the pandemic is rare. Coagulopathy has been associated with the inflammatory phase of coronavirus disease (COVID-19) and might be involved in this concurrency. CASES REPORT: We describe 2 patients with previous mild or no symptoms of COVID-19, admitted for acute stroke with recent/simultaneous myocardial infarction in whom admission polymerase chain reaction was negative but serologic testing diagnosed COVID-19. In these patients, concurrent stroke and myocardial infarction could have been promoted by COVID-19 infection. Management and evolution are detailed, and their contacts to confirm the COVID-19 infection. Pathogenic analysis of possible hypercoagulation state is described suggesting the hypothesis of endothelial dysfunction as the strongest mechanism involved in thrombus formation after the acute phase of COVID-19 infection. CONCLUSIONS: Our experience with these cases suggests that patients with mild symptoms can also present thromboembolic complications once the acute phase of COVID-19 infection has passed.